Premoštavanje jaza između države i društva / Bridging the Gap Between state and Society : Krizni štab kao ključni mehanizam etničkog čišćenja / Crisis Commitee as Ethnic Cleanising's Key Mechanisim (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
The paper examines and analyzes the role and position of the Crisis Committee as one of the key instruments in the ethnic cleansing in Bosnia and Herzegovina. The Crisis Committee Exhibition, War Presidency and similar bodies were drafted in the Yugoslav legislation in case of emergency or declared war. After SDS violently took power in 1992, it immediately used that authority and its law defined roles as one of the basic ethnic cleansing instruments in parts of Bosnia and Herzegovina where so called was declared Serbian Republic of Bosnia and Herzegovina against non-Serbs. The paper analyzes the array of measures and actions that Crisis Committees in the territory under their control were able to take and those taken in the process of deportation or extermination of non-Serbs. The paper’s aim is to put in the context within they took place in the local community or municipality ethnic cleansing as a set of measures and steps. The article demonstrates how the administrative or para-state apparatus and community coagulate into the ethniccleansing purpose and explores the “micro-mechanics” of ethnic cleansing and identifying the point at which there is a fusion of proto-state and society with one common purpose: ethnic cleansing. Ethnic cleansing takes place in the same environment, physical and institutional in which everyday life takes place, the same set of individual and group relationships and networks: the reality of ethniccleansing always takes place in an environment that is known to the perpetrator, that is relatively easy to control and isolate themselves from others similar units. Links between the state and society are the shortest, and their interaction is most intense in the physical and institutional environment in which everyday life takes place. The amount of evidence about the role and importance of the Crisis Committee in various stages of implementation of the Serbian irredentist policy of ethnic cleansing varies, but it can be concluded that it existed in various forms during the entire operation. Differences in the mandate arise from differences in historical and politically circumstances, the number and strength of the actors, and also from the fact that the Serbian political and military leadership learned from the mistakes and adapted tactics to new conditions.
Keywords: Crisis Committee; Bosnia and Herzegovina; ethnic cleansing